"We Wanted Change Yesterday!" The Promise and Perils of Poritikisi: Zimbabwean Farm Workers, Party Politics and Critical Social Science - Rutherford, Blair (Anthropologica, 2022)
In this article, I examine the entanglement of an emergent political imagination of "democracy" with the forms and meanings of poritikisi, party politics, for a group of farm workers involved in labour and land struggles in Zimbabwe from 1999 to 2003. In so doing, I seek to provide more insight into the on-going political and economic crises in this southern African country, while putting forth an analytic to ethnographically examine the effects of party politics. I also raise questions about the use of politics in critical social science.